The Global Horizon : Expectations of Migration in Africa and the Middle East - Schielke, Joska Samuli; Graw, Knut (Book collections on Project MUSE., 2012)
Although contemporary migration in and from Africa can be understood as a continuation of earlier forms of interregional and international migration, current processes of migration seem to have taken on a new quality. This volume argues that one of the main reasons for this is the fact that local worlds are increasingly measured against a set of possibilities whose referents are global, not local. Due to this globalization of the personal and societal horizons of possibilities in Africa and elsewhere, in many contexts migration gains an almost inevitable attraction while, at the same time, actual migration becomes increasingly restricted. Based on detailed ethnographic accounts, the contributors to this volume focus on the imaginations, expectations, and motivations that propel the pursuit of migration.--Provided by publisher.